2015
DOI: 10.22401/jnus.18.3.16
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and Cytotoxic Activity of Withania somnifera

Abstract: Withania somnifera (L) Dunal popularly known as 'Ashwagandha' had been used in folk medicine. Ten grams of leaves powder were used to extract the active substances as water, ethanol, and acetone extracts. The extracts were subjected to chemical analysis to identify the active components, Alkaloids, Glycosides, Saponins, Flavonoids, Fixed oil was present in ethanol, acetone and water extracts while terpene was absent in water extract, Proteins were not found in acetone extract, Tannins were absent in all types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Some authors reported cytotoxic activity of the adaptogens toward cell lines [ 47 , 48 ]. It has been reported that the silver nanoparticles of the Eleutherococcus senticosus dried stem parts demonstrated substantial cytotoxic and apoptotic effects on A549 lung cancer cells and HT29 colon cancer cells at a concentration of 10 μg/mL.…”
Section: Resultsmentioning
confidence: 99%
“…Some authors reported cytotoxic activity of the adaptogens toward cell lines [ 47 , 48 ]. It has been reported that the silver nanoparticles of the Eleutherococcus senticosus dried stem parts demonstrated substantial cytotoxic and apoptotic effects on A549 lung cancer cells and HT29 colon cancer cells at a concentration of 10 μg/mL.…”
Section: Resultsmentioning
confidence: 99%
“…It is an evergreen shrub, also known as winter cherry and Ashwagandha, has been an important property as herbal medicine [6]. W. somnifera is used in medicine, for antimicrobial activity, anti-fungal, antioxidant, anti-inflammatory, anticancer and other different diseases [7].The roots of W.somnifera contain different type of alkaloids, flavonoids, anolides, reducing sugars, amino acids, steroids, volatile oil, starch, glycosides, hentriacontane, dulcitol and withaniol [8][9]. So the aim is to study the effect of Withania somnifera roots extract on hyperlipidemia in male rabbits.…”
Section: Introductionmentioning
confidence: 99%